2021
DOI: 10.1111/jfpp.15735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of solid‐based feed concentration and water temperature on physicochemical, chlorophyll and antioxidative properties of Pandanus amaryllifolius leaf extract

Abstract: Pandan (Pandanus amarylifolius) leaves have been used for culinary purposes and also for medicinal uses due to having the benefit of health promoting as a diuretic, cardio-tonic and anti-diabetic (Jimtaisong & Krisdaphong, 2016;Wakte et al., 2010). In addition, the pandan leaves consist of glycosides, amino acids and vitamins, and contain phytochemicals like steroids, phenols, isoflavones, coumestrol, lignans, alkaloids, terpenoids, flavonoids, and saponins

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…P. amaryllifolius is a tropical plant in the Pandanus (screwpine) genus, commonly known as pandan (Setyaningsih et al 2019;Diyana et al 2021). P. amaryllifolius leaves are used in traditional medicine for the treatment of diabetes (Liaotrakoon et al 2021). A study evaluated the effect of crude extract from P. amaryllifolius leaves on blood glucose level and found that it had antihyperglycemic effects (Reshidan et al 2019).…”
Section: Inhibitory Power (%)mentioning
confidence: 99%
“…P. amaryllifolius is a tropical plant in the Pandanus (screwpine) genus, commonly known as pandan (Setyaningsih et al 2019;Diyana et al 2021). P. amaryllifolius leaves are used in traditional medicine for the treatment of diabetes (Liaotrakoon et al 2021). A study evaluated the effect of crude extract from P. amaryllifolius leaves on blood glucose level and found that it had antihyperglycemic effects (Reshidan et al 2019).…”
Section: Inhibitory Power (%)mentioning
confidence: 99%
“…The chlorophyll-bound Mg is released when the green plant undergoes thermal processing caused by the denaturation of lipoproteins and loses their protective effect, H + replaces Mg 2+ in tetrapyrrole to pheophytin, and the green color vanishes to form a brownish-yellow [41]; the reactions will be promoted by thermal and acidity conditions, oxidizing compounds, or active species [42,43]. The pheophytin formation rate will increase following the temperature increase in acidic conditions [44,45]. According to the variation in chlorophyll a and b values, in the thermal treatment process at 120 • C for 10-50 min, the color trend was significantly greater in seed coats (red and yellow) than in cotyledons (Figure 1c,d).…”
Section: Color Characteristicsmentioning
confidence: 99%